Development of novel, simple and low–cost microfluidic platform for supporting 3D dynamic cell culture - Nguyen, Nguyen Thanh Duong; Pham, Thu Uyen; Tran Dinh Thiet, (Vietnam Journal of Science and Technology, 2023)
Cell culture models more accurately would be of significant value to the medical field and pharmaceutical industry. To achieve this goal, microfluidic cell culture platforms are created and improved for modeling the native cell microenvironment because they can precisely reconstruct in vivo cellular behavior. In this study, a 3D low-cost microfluidic device is used to compare the difference between the static and dynamic environment in 3D cell culture. Cells were seeded in the microfluidic device, and to produce the fluidic flow, the pump was used with the set speed was 0.045ml/min. In 3D cell culture, the viability of cells was monitored by size growth of the spheroids for 7 days. All systems were designed and optimized without leakage of the medium. In the results, the 3D dynamic condition showed a faster increase in size than in the static condition. Overall, the study was prepared for microfluidic platforms with low-cost and simple settings. Moreover, the usage of 3D microfluidic to mimic in vivo returned favorable results that were expected for drug testing in the future.